Idiopathic focal intestinal perforation in low birth weight neonates - Kazez, Ahmet; Yekeler, Hayrettin; Turgut, Mehmet; Apak, Sami; Parmaksiz, Ergun (My University, 2003)
Aim: In this retrospective study, the patients with idiopathic focal intestinal perforation (IFIP), which was operated for intestinal perforation in our clinic, were reported, and the etiology and treatment of IFIP was reviewed. Method: The records and pathological samples of patients who were operated for intestinal perforation and diagnosed as IFIP between 1997 and 2001 in our clinics were reviewed retrospectively. Results: None of the known causes for neonatal intestinal perforation was present in the patients whose average weight was 1230 g (900-1750 g). Four of the perforations were in the antimesenteric side of the ileum and one at the splenic flexura of the colon. The patients were treated with primary anastomosis and discharged without any complication. The histopathological examinations revealed significant thinning in the muscular layer at the ileal perforations in two cases. Conclusion: The low mortality in IFIP patients' supports that the pathology is caused by local events. Primary anastomosis can be preffered to enterostomy in IFIP cases.
Düşük do?um tartili yenido?anlarda nedeni belirsiz yerel ba?irsak delinmesi
Keywords: Focal intestinal perforation; Low-birth-weight neonate